Public Policy Effectiveness of PMAY-G in Tamil Nadu: An Assessment of Rural Housing and Social Welfare - Dr. N. RAMESHKUMAR; Mr. T. SATHISPRABU. M.A., M.Phil. SET., Ph.D; Mr. R. VENKATESH. M.A., Ph.D (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Pradhan Mantri Awaas Yojana–Gramin (PMAY-G) has emerged as one of India's flagship rural housing programmes, aiming to provide safe, durable, and affordable housing to economically weaker rural households while promoting inclusive and sustainable development. This study evaluates the public policy effectiveness of PMAY-G in Tamil Nadu by assessing its contribution to rural housing improvement and social welfare outcomes. The research adopts a mixed-method approach, integrating quantitative data obtained from beneficiary households with qualitative insights gathered through interviews with local officials, Panchayat representatives, and beneficiaries. The analysis focuses on key policy dimensions, including beneficiary identification, transparency in implementation, financial assistance, housing quality, infrastructure convergence, and beneficiary satisfaction. The programme has also strengthened women's empowerment by encouraging property ownership in the names of women or jointly with spouses, thereby enhancing household decision-making and economic security. Despite these achievements, the study identifies challenges related to delays in fund disbursement, rising construction costs, regional disparities in implementation, shortages of skilled labour, and limited technical support during house construction.